2016
DOI: 10.1038/cr.2016.35
|View full text |Cite
|
Sign up to set email alerts
|

E2 enzymes: more than just middle men

Abstract: Ubiquitin-conjugating enzymes (E2s) are the central players in the trio of enzymes responsible for the attachment of ubiquitin (Ub) to cellular proteins. Humans have ∼40 E2s that are involved in the transfer of Ub or Ub-like (Ubl) proteins (e.g., SUMO and NEDD8). Although the majority of E2s are only twice the size of Ub, this remarkable family of enzymes performs a variety of functional roles. In this review, we summarize common functional and structural features that define unifying themes among E2s and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
442
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 442 publications
(453 citation statements)
references
References 146 publications
8
442
0
3
Order By: Relevance
“…A similar hydrophobic tethering mechanism for the donor ubiquitin (or donor Ubl) promotes catalytic efficiency and processivity of E2 enzymes (Stewart et al, 2016) and was shown to be stabilized by RING-type E3 enzymes (Dou et al, 2012(Dou et al, , 2013Plechanovová et al, 2012;Pruneda et al, 2012;Scott et al, 2014;Branigan et al, 2015;Wright et al, 2016) as well as SUMO-ligases (Reverter and Lima, 2005;Cappadocia et al, 2015;Streich and Lima, 2016). Importantly, however, the interactions of HECT E3 or E2 enzymes with the donor ubiquitin do not determine the linkage specificity of ubiquitin chain formation.…”
Section: Positioning Of the Donor Ubiquitin On The Hect C-lobementioning
confidence: 99%
“…A similar hydrophobic tethering mechanism for the donor ubiquitin (or donor Ubl) promotes catalytic efficiency and processivity of E2 enzymes (Stewart et al, 2016) and was shown to be stabilized by RING-type E3 enzymes (Dou et al, 2012(Dou et al, , 2013Plechanovová et al, 2012;Pruneda et al, 2012;Scott et al, 2014;Branigan et al, 2015;Wright et al, 2016) as well as SUMO-ligases (Reverter and Lima, 2005;Cappadocia et al, 2015;Streich and Lima, 2016). Importantly, however, the interactions of HECT E3 or E2 enzymes with the donor ubiquitin do not determine the linkage specificity of ubiquitin chain formation.…”
Section: Positioning Of the Donor Ubiquitin On The Hect C-lobementioning
confidence: 99%
“…The resulting E2 ~ Ub intermediate interacts with members of three different families of Ub E3 ligases (RING, HECT, and RING-in-between-RING (RBR)) that catalyze Ub conjugation to target proteins by distinct mechanisms 911 . The catalytic mechanism of RING E3s involves interactions between a zinc-binding RING domain and the E2 ~ Ub thioester intermediate that facilitates nucleophilic attack of the E2 ~ Ub thioester by a lysine on the target protein directly 911 . This contrasts with the mechanism of HECT E3s, which are structurally unrelated to RING E3s.…”
Section: Introductionmentioning
confidence: 99%
“…In unusual cases, ubiquitin can be linked to the free N-terminal amino group of a substrate or of ubiquitin, or even to serine or threonine side chains (forming ester bonds). In humans, there are two E1 enzymes and 32 E2s that are known to facilitate ubiquitin conjugation [1], while Saccharomyces cerevisiae has a single E1 and 11 E2s [2]. There are over 600 E3s encoded in the human genome and at least 51 in S. cerevisiae [2], and these enzymes collectively coordinate the ubiquitylation of thousands of substrates.…”
Section: Introductionmentioning
confidence: 99%
“…There are 14 human RBR E3s [5] and two in S. cerevisiae [1]. PARKIN, associated with the neurological condition Parkinson’s disease, is one of the best-studied RBR E3s [13].…”
Section: Introductionmentioning
confidence: 99%